Visualisasi Dinamika PHK Global dan Regional Menggunakan Tableau : Dampak Teknologi dan Ekonomi di Era Globalisasi - fianty, melissa; Kevin Aditya Hartono; Juanito Arvin William; Julius Calvin Saputra (Fakultas Teknik Universitas Hamzanwadi, 2024)
The development of information technology has influenced the structure of industries and global business practices, posing significant challenges related to job terminations or layoffs. This research aims to analyze the dynamics of global and Indonesian layoffs using data visualization tools such as Tableau, with a focus on their impact on economic growth, employment, and the achievement of SDG number 8. The research method involves five stages, from problem identification to conclusions, with an emphasis on layoff dynamics in the technology sector. The analysis results indicate that the year 2021 recorded the highest number of employee layoffs globally, particularly in North America, especially in the consumer and retail sectors. Industry analysis highlights the vulnerability of 'post-IPO' companies to layoffs, while early-stage startups tend to be more stable. In Asia, there has been an increase in layoffs, with India being the most affected country, while in Indonesia, the transportation sector, especially GoTo Group, recorded the highest number of layoffs. Recommendations include adaptive labor policies and support for affected workers to mitigate the socio-economic impact of layoffs globally